Analisis Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Sule Tailor Karawang - Ummul Azizah; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to evaluate the impact of Product Quality and Service Quality on Customer Satisfaction at Sule Tailor. The evaluation of customer and production data over the last three months indicates a decline, triggering the need for more intensive investigation into the elements contributing to customer satisfaction. In this context, a more comprehensive understanding of marketing management, Product Quality, and Service Quality becomes the focus. This study adopts a descriptive verificative quantitative approach to verify the hypothesis concerning the impact of Product and Service Quality on Customer Satisfaction. The findings of this research show that both product and service quality and consumer satisfaction levels recorded Cronbach’s Alpha values exceeding industry standards, indicating that the measurement tool used has a high level of reliability. Initially, the data distribution was not normal; however, after adjusting for extreme values, the distribution became normal. There was no evidence of excessive correlation between the Product Quality and Service Quality variables. The multiple linear regression analysis results indicate that both Product and Service Quality significantly affect Customer Satisfaction. Based on the coefficient of determination, it can be explained that about 37.5% of the variation in Customer Satisfaction is caused by the Product Quality and Service variables. It was confirmed through testing using the F-test and T-test that there is a significant relationship between Product Quality and Service Quality.